Efektifitas Kepala Sekolah dalam Meningkatkan Kinerja Guru Madrasah - ., Rumina; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2022)
Basically the level of teacher competence is influenced by factors from within the teacher itself, namely how the teacher behaves towards the work being carried out. While external factors that affect the professional competence of a teacher are the leadership of the principal where the principal is a functional teacher assigned to lead a school where the teaching and learning process is held or a place where there is interaction between teachers who give lessons and students who receive lessons. In the school education environment, the principal is fully responsible for managing and empowering teachers to continuously improve their work abilities. In addition, a school principal must also be able to assist teachers in providing learning experiences that are in accordance with the needs of students and the growing community. In this case, the role of the principal as a supervisor who deals with teachers every day must be applied. In improving the performance of teachers at MA Bahrul Ulum, it is achieved by means of In-Service education, namely by including training in accordance with their fields, both educators and existing education staff; teacher meetings called MGBS (study field teacher consultations) which are held both internally in schools and inter-school relations; personnel arrangements in accordance with their respective duties, discipline development, giving motivation and appreciation to teachers. The principal provides guidance and directs teachers, staff and students as well as providing encouragement and inspiration for school progress which is carried out on the agenda of the meeting every mid-semester at MA Bahrul Ulum.